The Profile of Multidrug Tuberculosis Regimen and Treatment Outcomes in Pulmonary MDR-TB Patients at the Tertiary Referral Hospital Dr. Soetomo, East Java, Indonesia: A Seven-Year Retrospective Study on Bedaquiline - Muhamad Frendy Setyawan; Ni Made Mertaniasih; Soedarsono Soedarsono (Acta Medica Indonesiana, 2023)
Background: The use of bedaquiline has been reported to minimize the number of lost to follow-up and fewer rejections from the patients. This study is the first to depict the use of bedaquiline. It aims to provide information related to the profile of the MDR-TB drug regimen in the last 7 years with the treatment outcomes of pulmonary MDR-TB patients at a tertiary referral hospital in East Java. Methods: This study was a retrospective, descriptive, and data analysis on 1053 pulmonary MDR-TB patients in tertiary referral hospital Dr Soetomo, East Java, Indonesia, with the SPSS software version 25 and Microsoft Excel 2021. Results: The study analyzed the  MDR-TB treatment regimen following the latest guidelines from WHO (2020) at a tertiary referral hospital in East Java. This study shows that a bedaquiline-containing regimen started in January 2015 to July 2022 with the percentage of distribution (1, 3, 11, 4, 18, 13, 29, 21)% consecutively in the regimen. The treatment outcome profile of MDR-TB patients shows the average percentage of cured (15%), died (12%), lost-to-follow-up cases (27%), moved to an individualized regimen or a different health facility (42%), and currently in the evaluation stage (4%). Overall from January 2017 to July  2022, the number of LTFU cases decreased (42, 46, 29, 19, 8, 4)%. However, the cured case fluctuated between 2017-2022 (16, 28, 26, 32)%  respectively after Bdq started to be included in the regimen regularly for treating RR/MDR-TB. Conclusion: After seven years of study, we revealed an association between adding bedaquiline to the regimen and the treatment success and decreasing lost-to-follow-up cases.